Pengembangan Sistem Pakar Diagnosa Gangguan Mental dengan Mesin Inferensi Menggunakan Algoritma Dempster-Shafer Theory - Hendra Mayatopani; Rino Subekti; Nunik Yudaningsih; Mochamad Sanwasih (Jurnal Buana Informatika, 2022)
Abstract. Development of a Mental Disorders Diagnostic System Using an Inference Engine Using the Dempster-Shafer Theory Algorithm. Patients with mental disorders in Indonesia show a high number. Mental disorders can be treated with special therapies by a psychologist or psychiatrist. However, the number of clinical psychologists and psychiatrists is not sufficient. So we need a system that can diagnose mental disorders and their treatment to prevent mental disorders as early as possible. Expert system development will face uncertainty due to the lack of information needed to decide. This study develops an expert system using the Dempster-Shafer theory algorithm as an inference engine to diagnose mental disorders. The system built can recognize mental disorders based on the symptoms felt by the patient. The system also includes explanations of mental disorders, causes, and treatment recommendations for patients. The accuracy test results show a comparison between the results of expert diagnostics and the system with a system accuracy level of 84%. Keywords: Dempster-Shafer theory, Disease diagnosis, Expert systems, Mental disorders, Uncertainty Abstrak. Penderita penyakit gangguan mental di Indonesia menunjukkan angka yang tinggi. Gangguan mental dapat diatasi dengan terapi-terapi khusus oleh psikolog atau psikiater. Akan tetapi jumlah psikolog klinis dan psikiater tidak mencukupi. Maka diperlukan sebuah sistem yang dapat mendiagnosa gangguan mental dan penanganannya sehingga dapat dicegah sedini mungkin. Pengembangan sistem pakar akan menghadapi ketidakpastian karena terjadi kurangnya informasi yang dibutuhkan untuk membuat sebuah keputusan. Penelitian ini mengembangkan sistem pakar menggunakan algoritma dempster-shafer theory sebagai mesin inferensi untuk mendiagnosis penyakit gangguan mental. Sistem yang dibangun dapat mengenali penyakit gangguan mental berdasarkan gejala yang dirasakan oleh pasien. Sistem juga menyertakan penjelasan mengenai penyakit gangguan mental, penyebab, dan rekomendasi pengobatan untuk pasien. Hasil pengujian akurasi menunjukkan perbandingan antara hasil diagnosa pakar dan sistem dengan tingkat akurasisistem mencapai 84%.Kata Kunci: Teori Dempster-shafer, Diagnosa penyakit, Sistem pakar, Gangguan mental, Ketidakpastian